Mucins trigger dispersal of Pseudomonas aeruginosa biofilms. (December 2018) - Co, Julia; Cárcamo-Oyarce, Gerardo; Billings, Nicole; Wheeler, Kelsey; Grindy, Scott; Holten-Andersen, Niels; Ribbeck, Katharina
Abstract Mucus is a biological gel that lines all wet epithelia in the body, including the mouth, lungs, and digestive tract, and has evolved to protect the body from pathogenic infection. However, microbial pathogenesis is often studied in mucus-free environments that lack the geometric constraints and microbial interactions in physiological three-dimensional mucus gels. We developed fluid-flow and static test systems based on purified mucin polymers, the major gel-forming constituents of the mucus barrier, to understand how the mucus barrier influences bacterial virulence, particularly the integrity ofPseudomonas aeruginosa biofilms, which can become resistant to immune clearance and antimicrobial agents. We found that mucins separate the cells inP .aeruginosa biofilms and disperse them into suspension. Other viscous polymer solutions did not match the biofilm disruption caused by mucins, suggesting that mucin-specific properties mediate the phenomenon. Cellular dispersion depended on functional flagella, indicating a role for swimming motility. Taken together, our observations support a model in which host mucins are key players in the regulation of microbial virulence. These mucins should be considered in studies of mucosal pathogenesis and during the development of novel strategies to treat biofilms. Biofilms: Mucins regulate bacterial dispersal in biofilms Biofilms are an important survival strategy for pathogenic bacteria includingPseudomonas aeruginosa and whilst mucins play a role the regulation of microbial virulence, microbial pathogenesis on mucosal tissues is often studied in mucin-free contexts. Here, Katharina Ribbeck and colleagues at the Massachusetts Institute of Technology used native purified mucin polymers and examined their effects on the integrity ofPseudomonas aeruginosa biofilms. The mucins dissolved the biofilms by separating the bacteria, which was not observed in other viscous alternative substances examined, but this did rely on functional bacterial motility. Here the authors provide evidence that mucins are involved in suppressing bacterial virulence and should be included in systems used to assess bacterial pathogenesis on mucosal tissues.